PTH stimulates PLCβ and PLCγ isoenzymes in rat enterocytes: influence of ageing - Gentili, Claudia Rosana (2001)
We previously reported that in rat duodenal cells (enterocytes), parathyroid hormone (PTH [1–34]: PTH) stimulates the hydrolysis of polyphosphoinositides by phospholipase C (PLC), generating the second messengers inositol trisphosphate (IP3) and diacylglycerol (DAG) and that this mechanism is severely altered in old animals. In the present study, we show that PTH [1–34]-dependent IP3 release in young rats was blocked to a great extent by an antibody against guanine nucleotide binding protein Gαq/11, indicating that the hormone activates a β isoform of PLC coupled to the α subunit of Gq/11. In addition, PTH rapidly (within 30 s, with maximal effects at 1 min) stimulated tyrosine phosphorylation of PLCγ in a dose-dependent fashion (10−10–10−7 M). The hormone response was specific as PTH [7–34] was without effects. The tyrosine kinase inhibitors, genistein (100 μM) and herbimycin (2 μM), suppressed PTH-dependent PLCγ tyrosine phosphorylation. Stimulation of PLCγ tyrosine phosphorylation by PTH [1–34] greatly decreased with ageing. PP1 (10 μM), a specific inhibitor of the Src family of tyrosine kinases, completely abolished PLCγ phosphorylation. The hormone-induced Src tyrosine dephosphorylation, a major mechanism of Src activation, an effect that was blunted in old animals. These results indicate that in rat enterocytes PTH generates IP3 mainly through G-protein-coupled PLCβ and stimulates PLCγ phosphorylation via the nonreceptor tyrosine kinase Src. Impairment of PTH activation of both PLC isoforms upon ageing may result in abnormal hormone regulation of cell Ca2+ and proliferation in the duodenum.